Late Antiquity : A Very Short Introduction - Clark, Gillian (E. Gillian) (Oxford, New York Oxford University Press, 2011)
The time known as Late Antiquity (c.300-c.800) was a fascinatingly diverse and important period which saw the 'Fall of Rome' and the growth of Christianity and Islam. Gillian Clark explores its historical controversies, introducing the main characters and themes, and demonstrating the transition between the medieval and ancient.
Include Index and Illustration
Keywords: Civilization, Ancient -- History, Ancient